Feasibility of measuring selenium in humans using in vivo neutron activation analysis. (22nd September 2015) - Tahir, S N A; Chettle, D R; Byun, S H; Prestwich, W V
Abstract: Selenium (Se) is an element that, in trace quantities, plays an important role in the normal function of a number of biological processes in humans. Many studies have demonstrated that selenium deficiency in the body may contribute to an increased risk for certain neoplastic, cardiovascular, osseous, and nervous system diseases including retardation of bone formation. However, at higher concentrations Se is cytotoxic. For these reasons it is desirable to have a means of monitoring selenium concentration in humans. This paper presents the outcome of a feasibility study carried out for measuring selenium in humans using in vivo neutron activation analysis (IVNAA). In this technique a small dose of neutrons is delivered to the organ of interest, the neutrons are readily captured by the target nuclei, and the γ -rays given off are detected outside of the body. For the present study, human hand (bone) tissue equivalent phantoms were prepared with varying amounts of Se. These were irradiated by a low energy fast neutron beam produced by the 7 Li( p, n ) 7 Be reaction employing the high beam current Tandetron accelerator. The counting data saved using a 4 π NaI(TI) detection system were analyzed. The selenium was detected via the neutron capture reaction, 76 Se( n, γ ) 77m Se, whereas calcium was detected through the 48 Ca( n, γ ) 49 Ca reaction for the purpose of normalization of the Se signals to the calcium signals. From the calibration lines drawn between Se/Ca concentrations and Se/Ca counts ratio, the minimum detection limits (MDLs) were computed for two sets of phantoms irradiated under different irradiation parameters. In this study the optimized MDL value was determined to be 81 ng g −1 (Se/phantom mass) for an equivalent dose of 188 mSv to the phantom. This MDL was found at least 10 times lower than the reported data on Se concentration measured in bone tissues. It was concluded that the NAA technique would be a feasible means of performing in vivo measurements of selenium in humans. Currently the data on in vivo measurement of selenium in humans are limited; the results of the present study would greatly contribute to the present data.